Design and Experimental of Portable Conical Solar Still and Study Parameters - Khadija .A.Mohammad, Yaseen. H. Mahmood (Pakistan Journal of Medical & Health Sciences, 2022)
The lack of drinking water in remote and semi-desert areas, as a result of the lack of fuel and its high price. The trend towards renewable energy, including solar energy, has increased. In this paper a conical type solar distiller has been manufactured and practically experimented with the purposes of distilling the water of wells in Mosul . He studied the high temperature distilled over time using a black distilled basin first. Then add the black marble to the basin secondly. And added bitumen the third. Found high water temperature, and glass whenever added heat absorbing and slowly lost substances. Also, the addition of these substances increased productivity and efficiency. Also demonstrated in practice the effectiveness of the distiller being exposed to solar radiation from all directions. Keywords: Renewable Energy , Solar energy, Solar thermal ,Solar Distiller , phase change material .water purification , Remove salts from water.